The Implication of Conjunctive Element Shifts in the Translation of Argumentative Texts (KEMANUSIAAN The Asian Journal of Humanities, 2018)
This study attempts to identify the implication of conjunctive element shifts in the Chinese translation of argumentative column articles by an established columnist. More specifically, this study focuses on the implication of a cohesive shift, which includes explicitations, implicitations, shifts and wrong translations of conjunctive elements in the translated text. The texts in this study are argumentative in nature, and the use of conjunctive elements is pivotal in guiding the reader on the flow of the argument at hand. Through indepth analysis and observation, it is found that changes in conjunctive elements can affect a translation in six possible ways: altering the intensity of the message, shifting the focus of the message, altering the tone and manner of the texts, causing repetitious and intrusive translations, changing the interpretation of the text, and altering the conversational-like element in the source text.